Description of the larvae of Drusus radovanovici septentrionis Marinkovic-Gospodnetic, 1976 and Drusus croaticus Marinkovic-Gospodnetic, 1971 (Trichoptera: Limnephilidae) from Bosnia and Herzegovina, and Croatia - Kučinić, Mladen; Previšić, Ana; Gottstein, Sanja; Hrašovec, Boris; Stanić-Koštroman, Svjetlana; Pernek, Milan; Delić, Antun (Zootaxa, 2008)
A description of the hitherto unknown larvae of Drusus radovanovici septentrionis Marinković-Gospodnetić, 1976 and Drusus croaticus Marinković-Gospodnetić, 1971 is given. The most important diagnostic features enabling separation from larvae of the other Drusinae are listed and illustrated. Larvae of D. croaticus are distinguished by the combination of specific morphological features (e.g. shape of head and pronotum, the absence of mandible teeth, the absence of prominent, black median setae on frontal margin of pronotum etc.). Besides the above mentioned, larvae of D. radovanovici septentrionis are primarily distinguished by distinct spinules on the head capsule. Some ecological notes are given and the life cycle of both species is discussed. Regarding the feeding behaviour, both analyzed species seem to be predominantly grazers. Both species were recorded in different spring types in the Dinarides. D. radovanovici septentrionis is known only from three springs in Bosnia and Herzegovina (springs of the Rivers Pliva, Bistrica and Sturba), while D. croaticus was recorded in 19 different springs in Croatia. Additionally, all Trichopteran species recorded from the sampled springs are listed.